STX17 dynamically regulated by Fis1 induces mitophagy via hierarchical macroautophagic mechanism - Hongxu Xian (Nature Portfolio, 2019)
Mitophagy plays a critical role in cellular homeostasis, and PINK1/Parkin-mediated mitophagy is the most thoroughly characterized. Here, Xian et al. show that STX17 induces mitophagy via a macroautophagy pathway regulated by Fis1, by a PINK1/Parkin-independent route.